“Awakened Muse” by Ihor Kalynets in the interartistic dialogue with Oleksa Novakivskyi - Hryhorii Savchuk (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2024)
The purpose of the article is to provide an alternative reading of the title of Ihor Kalynets’s collection “Awakened Muse” based on an intermedial analysis of poems written under the influence of Olexander Novakivskyi’s paintings. Ihor Kalynets felt the nerve of rebellion and the all-consuming element of music in the livestory and creative work of the artist from Lviv and conveyed them through the poem “Muse”. The poem presents a collective image of Anna-Maria, the wife, who inspired O. Novakivskyi’s artistic work, and who really was his muse. The created visual image continues the theme of “Stabat Mater” (“Grieving Mother”) in the worldwide art. The fact is that the rebellious, expressive nature of the artist’s work required its opposite for balance, which was embodied in the figure of his wife and muse Anna-Maria. In I. Kalynets’s interpretation, Anna-Maria “had” to be a muse for her husband, that is, the wife “had” to devote herself to the service of art, realizing that she would have to experience certain sacrifices for this.